Safety and tolerability of edivoxetine as adjunctive treatment to selective serotonin reuptake inhibitor antidepressants for patients with major depressive disorder - Martinez, James M; Ferguson, Margaret B; Pangallo, Beth A; Oakes, Tina M; Sparks, JonDavid; Dellva, Mary Anne; Zhang, Qi; Liu, Peng; Bangs, Mark; Ahl, Jonna; Goldberger, Celine (Drugs in Context, 2015)
The aim of this analysis was to assess the safety profile of edivoxetine as adjunctive treatment to selective serotonin reuptake inhibitor (SSRI) antidepressants. A pooled analysis was conducted on data obtained from the integrated safety database of edivoxetine as adjunctive treatment to SSRIs. Safety and tolerability assessments included discontinuation rates, spontaneously reported treatment-emergent adverse events (TEAEs), clinical laboratory tests, blood pressure (BP) and pulse, and electrocardiograms (ECGs). The analysis included 1260 patients treated with adjunctive edivoxetine and 806 treated with adjunctive placebo. Study completion rates were 85.2% and 84.5% (p=0.994), respectively. Discontinuations due to adverse events were 4.9% and 3.5% (p=0.07), respectively. Significantly more patients in the adjunctive edivoxetine group compared with adjunctive placebo group reported at least one TEAE (56.8 vs 43.7%, p<0.001). The most common TEAEs (occurred ≥5% frequency) were hyperhidrosis, nausea, and tachycardia. Mean changes in sitting BP and pulse at the last visit were increased significantly in patients treated with adjunctive edivoxetine compared with adjunctive placebo (SBP: 2.7 vs 0.5 mm Hg, p<0.001; DBP: 4.1 vs 0.8 mm Hg, p<0.001; pulse: 8.8 vs -1.3 bpm, p<0.001). There were no clinically significant changes in laboratory measures. The tolerability and safety profile of edivoxetine as adjunctive treatment to SSRI antidepressants was consistent with its norepinephrine reuptake inhibitor mechanism of action, and was comparable with edivoxetine monotherapy treatment in patients with major depressive disorder.